Into the mist : a novel - Cast, P. C. (Crooked Lane, 2022)
"From #1 New York Times bestselling author P. C. Cast comes INTO THE MIST, the first book in a pulse-pounding dystopian duology for our times. Practical Magic meets Station Eleven in this gripping take on female power and the inevitable, destructive path of violent patriarchies. As men fall to the mist, the age of womankind begins to rise. The world as we know it ends when an attack on the U.S. unleashes bombs that deliver fire and biological destruction. Along with sonic detonations and devastating earthquakes, the bombs have also brought the green mist. If breathed in, it is deadly to all men--but alters the body chemistry of many women, imbuing them with superhuman abilities. A group of high school teachers heading home from a conference experiences firsthand the strength of these new powers. Mercury Rhodes is the Warrior, possessing heightened physical powers. Stella Carver is the Seer, with a sixth sense about the future. Imani Andrews is the Watcher, with a rare connection to the earth. Karen Gay is the Priestess, demonstrating a special connection with Spirits. And Gemma Jenkins is the Healer, a sixteen-year-old student who joins the group after losing her parents. As they cross the Pacific Northwest, trying to find a safe place to ride out the apocalypse, the women soon learn they can't trust anyone, and with fresh danger around every corner, it will take all their powers to save themselves--and possibly the world. With timely commentary on power and community, Into the Mist delivers a thrilling and fantastical future that is equal parts a feminist commentary and an amazing, witty adventure filled with wine and women--as only P.C. Cast's brilliant storytelling can bring to life."--Provided by publisher.